Customer Engagement: Is It Important to Housing Purchase Intention? - Perwira, Desna Ronaldy Yoga; Masnita, Yolanda; Kurniawati, Kurniawati; Ali, Jati Kasuma (Media Ekonomi dan Manajemen, 2024)
Social media platforms have added new ways to get information that can influence the purchase intent, including housing purchasing. Since there is a paucity of research that investigates the relationship between consumers' access to social media and their intention to purchase a house, the aim of this study is to determine whether social media activities as marketing tools influence the intent of people in house purchasing, especially when comes to customer engagement.Â Â  The results of this study are expected to give marketing managers of real estate companies different ideas about how to run each of the official social media platforms to get people to buy the houses. The data collection process involved the participation of 284 individuals who completed online questionnaires. The collected data was subsequently analyzed using statistical software packages such as SPSS and AMOS to derive meaningful findings. This study found that SMMA activities positively influence brand trust, as well as Brand Trust and Purchase Intention, but the primary focus of this research is to investigate the impact of these variables on house purchase intention, with a particular emphasis on the role of customer engagement.